Understanding The Role of Affordance Existence Barriers in SMEs Digitalization Failure - Muhammad, Ghifary; Er, Mahendrawathi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The failure of digitization in small and medium-sized enterprises (SMEs) is commonly not driven by the absence of technology, instead by lack of cognition readiness to utilize it. This research focuses on the affordance stage to explore how the potential of technology fails to emerge in medium-sized SMEs due to two barriers, reliance on outdated legacy systems and absence of digital growth mindset. By applying multiple case studies, the data conducted with semi-structured interviews, field observation, and document review of medium-sized SMEs in Indonesia and analyzed using Gioia Methodology. The findings reveal that in Firm A, only 34.88% of Point of Sales (POS) system features were adopted, while in Firm B, adoption increased from 20.93% to 49.43% but remained partial and inconsistent. The findings also highlight that even though digital tools such as Point of Sales (POS) systems are technically available, digitalization are considered unnecessary or difficult to use due to strongly established preferences for manual control and the absence of mindset focused on digitalization. The novelty of this study depends on the refinement of affordance theory by explicitly identifying barriers at the existence stage, an area that has been underexplored in previous studies. This research contributes to the literature by offering conceptual refinement of digitalization failure by focusing on existence of affordance and providing practical implications for SME owners, consultants, and policymakers seeking to design more adaptive and cognitively aware digitalization strategies.